The effectiveness of service processes in the warehouse section in delivering materials to the end users in 1st Silicon / Jubri Atak - Atak, Jubri (2005)
This project paper attempts to study the Effectiveness of Service Processes in the Warehouse Section in delivering materials to the end users in 1st Silicon. Those end users had their inventoried materials located in all warehouses that were managed by the warehouse personnel under Warehousing Department. The researcher tried to find the problems and objectives of the project paper, and thereafter analyzed the significant of the study, which would benefit both the Warehouse Department and the end users of the materials. The general activities of the warehouse were enhanced by the literature review that were collected from external sources and relate to the warehouse activities in 1st Silicon. In the research methodology and design, the research er described the methods on how to collect data and procedures during the interview processes. Finding and data analysis were based on the graph extracted from the questionnaires. The finding revealed that the services rendered by the warehouse personnel was good, with majority of the respondents were satisfied with it.